New insight into the analgesic recipe: A cohort study based on smart patient-controlled analgesia pumps records - Yiyan Song; Qiulan He; Wenzhong Huang; Lu Yang; Shaopeng Zhou; Xiaoyu Xiao; Zhongxing Wang; Wenqi Huang (Frontiers in Pharmacology, 2022)
Purpose: Intravenous patient-controlled analgesia (IV-PCA) has been widely used; however, regimen criteria have not yet been established. In China, the most often used opioid is sufentanil, for which repeated doses are a concern, and empirical flurbiprofen axetil (FBP) as an adjuvant. We hypothesized that hydromorphone would be a better choice and also evaluated the effectiveness of FBP as an adjuvant.Methods: This historical cohort study was conducted in two tertiary hospitals in China and included 12,674 patients using hydromorphone or sufentanil for IV-PCA between April 1, 2017, and January 30, 2021. The primary outcome was analgesic insufficiency at static (AIS). The secondary outcomes included analgesic insufficiency with movement (AIM) and common opioid-related adverse effects such as postoperative nausea and vomiting (PONV) and dizziness.Results: Sufentanil, but not the sufentanil-FBP combination, was associated with higher risks of AIS and AIM compared to those for hydromorphone (OR 1.64 [1.23, 2.19], p < 0.001 and OR 1.42 [1.16, 1.73], p < 0.001). Hydromorphone combined with FBP also decreased the risk of both AIS and AIM compared to those for pure hydromorphone (OR 0.74 [0.61, 0.90], p = 0.003 and OR 0.80 [0.71, 0.91], p < 0.001). However, the risk of PONV was higher in patients aged ≤35 years using FBP (hydromorphone-FBP vs. hydromorphone and sufentanil-FBP vs. hydromorphone, OR 1.69 [1.22, 2.33], p = 0.001 and 1.79 [1.12, 2.86], p = 0.015).Conclusion: Hydromorphone was superior to sufentanil for IV-PCA in postoperative analgesia. Adding FBP may improve the analgesic effects of both hydromorphone and sufentanil but was associated with an increased risk of PONV in patients <35 years of age.